Pituitary Dysfunction After Aneurysmal Subarachnoid Hemorrhage: A Systematic Review and Meta-analysis. Issue 2 (August 2016) - Can, Anil; Gross, Bradley A.; Smith, Timothy R.; Dammers, Ruben; Dirven, Clemens M.F.; Woodmansee, Whitney W.; Laws, Edward R.; Du, Rose
Abstract : BACKGROUND: The prevalence of hypothalamic-pituitary dysfunction after aneurysmal subarachnoid hemorrhage has not been precisely determined, and conflicting results have been reported in the literature. OBJECTIVE: To perform a systematic review and meta-analysis investigating the prevalence of pituitary insufficiency after aneurysmal subarachnoid hemorrhage and to focus on basal serum and dynamic test differences. METHODS: The prevalence of pituitary dysfunction was quantified at 3 to 6 months and >6 months after aneurysmal subarachnoid hemorrhage. Proportions were transformed with the logit transformation. A subgroup analysis was performed focusing on the differences in outcome between basal serum and dynamic tests for the diagnosis of growth hormone deficiency (GHD) and secondary adrenal insufficiency. RESULTS: Overall prevalence of hypopituitarism differed considerably between studies, ranging from 0.05 to 0.45 in studies performed between 3 and 6 months after the event and from 0 to 0.55 in long-term studies (>6 months), with pooled frequencies of 0.31 (95% confidence interval [CI]: 0.22-0.43) and 0.25 (95% CI: 0.16-0.36), respectively. Pooled frequency of GHD at 3 to 6 months was 0.14 (95% CI: 0.08-0.24). At >6 months, GHD prevalence was 0.19 (95% CI: 0.13-0.26) overall, but ranged from 0.15 (95% CI: 0.06-0.33) with the insulin tolerance test to 0.25 (95% CI: 0.15-0.36) using the growth hormone releasing hormone + arginine test. CONCLUSION: Hypopituitarism is a common complication in patients with aneurysmal subarachnoid hemorrhage, with GHD being the most prevalent diagnosis. We showed that variations in prevalence rates in the literature are partly due to methodological differences among pituitary function tests. ABBREVIATIONS: ACTH, adrenocorticotropic hormone aSAH, aneurysmal subarachnoid hemorrhage GHD, growth hormone deficiency GHRH, growth hormone-releasing hormone GST, glucagon stimulation test IGF, insulin-like growth factor 1 ITT, insulin tolerance test SAH, subarachnoid hemorrhage Abstract : Supplemental Digital Content is Available in the Text.